THE EFFECT OF STEM ACTIVITIES ON PRESCHOOL STUDENTS' SCIENTIFIC PROCESS SKILLS - Keçeci, Gonca; Aydın, Tuba; Zengın, Fıkrıye Kırbag (My University, 2019)
STEM education is recommended to be started in early childhood. This study was conducted todetermine the effect of STEM activities on preschool students' scientific process skills. The studywas carried out with a total of 24 students (11 control groups, 13 experimental groups) who wereeducated in a preschool in Elazığ province during 2017-2018 academic year. In this study, quasiexperimental design was used. The study consisted of activities involving STEM applications,robotic studies and fun science experiments for 11 weeks. In the study, robotics studies andamusing science experiments were integrated and applied in accordance with STEMunderstanding. Applications lasted for 11 weeks. In the control group, the current program hasbeen adhered to during the course process. The scientific process skill test (SPST) was used as adata collection tool in the study. The pre-test and posttest scores of scientific process skill testwere analyzed using the Mann-Witney U test. When the test statistic was examined, it wasconcluded that the students in the experimental and control groups had a statistically significantdifference between the SPST post-test scores and sub-dimensions of SPST (p <.01). STEMactivities have been found to contribute to preschool students ‘scientific process skills.
Keywords: Biyoloji; Eğitim; Eğitim Araştırmaları; Fizik; Atomik ve Moleküler Kimya; Matematik; Metalürji Mühendisliği